Vitamin B12 ointment containing avocado oil in the therapy of plaque psoriasis - Markus Stücker; Ulrike Memmel; Matthias Hoffmann; Joachim Hartung; Peter Altmeyer (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2001)
Background: There are already many effective topical therapies available for use in the treatment of chronic plaque psoriasis. Unfortunately, these treatments are often associated with a not insignificant risk of undesirable effects. Objective and methods: In the randomized, prospective clinical trial discussed in the following, the therapeutic effects of the standard vitamin D3 analog calcipotriol were evaluated against those of a recently developed vitamin B12 ointment containing avocado oil preparation in an intraindividual right/left-side comparison. The efficacy of vitamin B12 in the treatment of psoriasis has already been demonstrated. The trial collective consisted of 13 patients, ten men and three women, with chronic plaque psoriasis. The observation period was 12 weeks; the effects of therapy were assessed on the basis of a PASI score adapted to the right/left-side comparison technique, the subjective evaluations of the investigator and patients and the results of 20 MHz sonography. Results: There was more rapid development of beneficial effects with use of calcipotriol in the initial 8 weeks, although differences in effects were significant only at the time point therapy week 8 (p<0.05). After 12 weeks, neither the PASI score nor 20 MHz sonography showed significant differences between the two treatments. While the efficacy of the calcipotriol preparation reached a maximum in the first 4 weeks and then began subsequently to subside, the effects of the vitamin B12 ointment containing avocado oil remained at a constant level over the whole observation period. This would indicate that the vitamin B12 preparation containing avocado oil may be suitable for use in long term therapy, a hypothesis further supported by the fact that the investigator and patients assessed the tolerability of the vitamin B12 ointment containing avocado oil as significantly better in comparison with that of calcipotriol. Conclusion: The results of this clinical trial provide evidence that the recently developed vitamin B12 ointment containing avocado oil has considerable potential as a well tolerated, long term topical therapy of psoriasis.
Keywords: 519; Psoriasis; Vitamin B12 ointment containing avocado oil; Calcipotriol